Plasma Generator Design For Citarum River Water Purification and Sterilization After Initial Filterization - Multi, Abdul; Purnomo, Agung Sigit; Wahyuningsih, Eko Sri (International Journal of Advanced Multidisciplinary, 2025)
Mountain water is the main raw material in drinking water depots and water from drinking water companies is known as healthy water and good for consumption, people think this water is the best, while the population, costs increase every year, and transportation terrain is increasingly difficult, how long can this condition last. River water and soil that are properly processed, namely filtration and ozone disinfection, can be a substitute for mountain water, by designing, creating, and implementing appropriate technology to process river water and soil so that it is suitable for consumption. Plasma Generator is a tool for producing Ozone, which is used as a strong disinfectant and without residue in water. This tool uses a spiral cylinder electrode method with Dielectric Barrier Discharge (DBD). Corona release occurs between high voltage electrodes of 13.28 kV from a distance between electrodes of 0.5 mm, capable of producing ozone that can purify dirty water and sterilize water containing E. coli bacteria.